Ex situ solid electrolyte interface modification with chalcogenides for lithium metal anodes
A lithium-containing anode structure with a SEI membrane stack addresses the limitations of lithium-ion batteries by enhancing cycle life and reducing resistance through ex situ formation of chalcogenide films, resulting in improved performance.
Patent Information
- Application Number
- JP2023190502
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-11-09
- Filing Date
- 2023-11-08
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2038-10-02
AI Technical Summary
Current lithium-ion batteries face challenges with limited energy capacity, cycle life, and high internal resistance, which hinder their application in high-performance energy storage devices.
The development of a lithium-containing anode structure with a solid electrolyte interface (SEI) membrane stack composed of chalcogenide films, lithium oxide, lithium carbonate, and lithium fluoride, formed ex situ during manufacturing to enhance stability and efficiency.
The SEI membrane stack suppresses lithium dendrite growth, improving cycle performance and reducing internal resistance, leading to higher capacity retention and faster charging capabilities.
Smart Images

Figure 0007618005000001 
Figure 0007618005000002 
Figure 0007618005000003
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE
[0001] Embodiments described herein relate generally to metal electrodes, and more specifically to lithium-containing anodes, high performance electrochemical devices, such as secondary batteries, that include said lithium-containing electrodes, and methods for making same. [Background technology]
[0002]
[0002] Rechargeable electrochemical storage systems are gaining importance in many areas of daily life. Large capacity energy storage devices, such as lithium-ion (Li-ion) batteries and capacitors, are being used in an increasing number of applications, including portable electronics, medical, transportation, grid-connected large energy storage, renewable energy storage, and uninterruptible power supplies (UPS). In each of these applications, the charge and discharge time and capacity of the energy storage device are important parameters. In addition, the size, weight, and / or cost of such energy storage devices are also important parameters. Furthermore, low internal resistance is essential for high performance. The lower the resistance, the fewer constraints the energy storage device encounters in delivering electrical energy. For example, in the case of a battery, the internal resistance affects performance by reducing the total amount of useful energy stored by the battery as well as the battery's ability to deliver large currents.
[0003]
[0003] Li-ion batteries are believed to have the best chance of achieving the required capacity and cycle count, but as currently constructed, Li-ion batteries often lack the energy capacity and charge / discharge cycle count for these growing applications.
[0004]
[0004] Thus, there is a need in the art for faster charging, higher capacity energy storage devices that improve cycle count and can be manufactured more cost effectively. There is also a need for energy storage device components that reduce the internal resistance of the energy storage device. Summary of the Invention
[0005]
[0005] The embodiments described herein relate generally to metal electrodes, more specifically lithium-containing anodes, high performance electrochemical devices, such as secondary batteries, including said lithium-containing electrodes, and methods of fabrication thereof. In one embodiment, an anode electrode structure is provided. The anode electrode structure comprises a current collector including copper. In one embodiment, the anode structure comprises a copper film. The anode electrode structure further comprises a lithium metal film formed on the current collector. The anode electrode structure further comprises a solid electrolyte interface (SEI) film stack formed on the lithium metal film. The SEI film stack comprises a chalcogenide film formed on the lithium metal film. In one embodiment, the SEI film stack further comprises a lithium oxide film formed on the chalcogenide film. In one embodiment, the SEI film stack further comprises a lithium carbonate film formed on the lithium oxide film. In another embodiment, the SEI film stack further comprises lithium fluoride formed on the chalcogenide film.
[0006] In another embodiment, an anode electrode structure is provided. The anode electrode structure comprises a current collector comprising copper. The anode electrode structure further comprises a lithium metal film formed on the current collector. The anode electrode structure further comprises a solid electrolyte interface (SEI) film stack formed on the lithium metal film. The SEI film stack includes a lithium oxide film, a lithium carbonate film formed on the lithium oxide film, and a chalcogenide film formed on the lithium carbonate film. In one embodiment, the SEI film stack further includes a lithium nitride film formed between the lithium metal film and the lithium oxide film.
[0007] In another embodiment, a method is provided. The method includes forming a lithium metal film on a current collector, the current collector including copper. The method further includes forming an SEI film stack on the lithium metal film. Forming the SEI film stack includes forming a chalcogenide film on the lithium metal film, the chalcogenide film being selected from the group of bismuth chalcogenide, copper chalcogenide, and combinations thereof. In one embodiment, the SEI film stack includes a lithium fluoride (LiF) film, a lithium carbonate (Li 2 CO 3 ) film, lithium oxide film, lithium nitride (Li 3 N) membrane, and combinations thereof.
[0008]
[0008] So that the above-mentioned features of the present disclosure can be understood in detail, a more particular description of the above briefly summarized embodiments can be made by reference to the embodiments, some of which are illustrated in the accompanying drawings. It should be noted, however, that the accompanying drawings illustrate only typical embodiments of the present disclosure and therefore should not be considered as limiting the scope of the present disclosure, which may admit of other equally effective embodiments. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 shows a schematic cross-sectional view of one embodiment of an energy storage device incorporating an electrode structure having a solid electrolyte interface (SEI) film stack formed according to embodiments described herein. [Diagram 2] 1 illustrates a cross-sectional view of one embodiment of a double-sided anode electrode structure having a solid electrolyte interface (SEI) film stack formed in accordance with embodiments described herein. [Diagram 3] 1 illustrates a cross-sectional view of another embodiment of a double-sided anode electrode structure having a solid electrolyte interface (SEI) film stack formed in accordance with embodiments described herein. [Figure 4]1 illustrates a cross-sectional view of another embodiment of a double-sided anode electrode structure having a solid electrolyte interface (SEI) film stack formed in accordance with embodiments described herein. [Diagram 5] 1 illustrates a cross-sectional view of another embodiment of a double-sided anode electrode structure having a solid electrolyte interface (SEI) film stack formed in accordance with embodiments described herein. [Figure 6] 1 illustrates a cross-sectional view of another embodiment of a double-sided anode electrode structure having a solid electrolyte interface (SEI) film stack formed in accordance with embodiments described herein. [Figure 7] 1 shows a process flow diagram summarizing one embodiment of a method for forming an anode electrode structure having a solid electrolyte interface (SEI) film stack according to embodiments described herein. [Figure 8] 1 shows a process flow diagram summarizing one embodiment of another method for forming an anode electrode structure having a solid electrolyte interface (SEI) film stack according to embodiments described herein. [Figure 9] 1 shows a process flow diagram summarizing one embodiment of another method for forming an anode electrode structure having a solid electrolyte interface (SEI) film stack according to embodiments described herein. [Figure 10] 1 shows a process flow diagram summarizing one embodiment of another method for forming an anode electrode structure having a solid electrolyte interface (SEI) film stack according to embodiments described herein. [Figure 11] 1 shows a schematic diagram of an integrated processing tool for forming an anode electrode structure according to embodiments described herein. [Figure 12A] 1 is a graph showing cell voltage change versus time for a symmetric lithium cell (1 hour cycle) at a current density of 0.25 mA / cm2. [Figure 12B] 1 is a graph showing cell voltage change versus time for a symmetric lithium cell (1 hour cycle) at a current density of 0.25 mA / cm2. [Figure 12C]1 is a graph showing cell voltage change versus time for a symmetric lithium cell (1 hour cycle) at a current density of 0.25 mA / cm2. [Figure 12D] 1 is a graph showing cell voltage change versus time for a symmetric lithium cell (1 hour cycle) at a current density of 0.25 mA / cm2. [Figure 13] 1 is a graph of impedance spectra for a Li / Li symmetric cell using a chalcogenide modified interface according to embodiments described herein. [Figure 14] 1 is a graph showing a comparison between a lithium control sample and a chalcogenide modified interface according to embodiments described herein. [Figure 15] 1 is a SEM image of lithium in a control cell and a cell having a chalcogenide modified interface according to embodiments described herein. [Figure 16] 1 is a graph showing discharge capacity versus cycle number for a bare lithium metal anode and a lithium metal anode protected with a chalcogenide-modified interface according to embodiments described herein. [Figure 17] 1 is a graph showing cell voltage versus capacity at various discharge rates (0.1 C to 5 C) for a lithium metal anode protected with a chalcogenide-modified interface according to embodiments described herein. [Figure 18] 1 is a graph showing the corresponding variation of discharge capacity versus C-rate for a lithium metal anode protected with a chalcogenide-modified interface according to embodiments described herein. [Figure 19] 1 is a graph comparing discharge capacity retention rates at various discharge rates. [Figure 20] 1 is a graph comparing the variation in charge rate capacity versus C-rate for a control sample and a lithium metal anode protected with a chalcogenide-modified interface according to embodiments described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010]
[0029] To facilitate understanding, identical elements common to the figures have been designated using the same reference numerals wherever possible. It is contemplated that elements and features of one embodiment may be beneficially incorporated in other embodiments without further recitation.
[0011]
[0030] The following disclosure describes high performance electrochemical devices, such as lithium-containing electrodes, secondary batteries including lithium-containing electrodes, and methods of making the same. Specific details are set forth in the following description and in Figures 1-20 to provide a thorough understanding of the various embodiments of the present disclosure. Other details describing well-known structures and systems often associated with electrochemical cells and secondary batteries are not set forth in the following disclosure to avoid unnecessarily obscuring the description of the various embodiments.
[0012]
[0031] Many of the details, dimensions, angles, and other features shown in the drawings are merely illustrative of particular embodiments. Thus, other embodiments can have other details, components, dimensions, angles, and features without departing from the spirit or scope of the present disclosure. Additionally, further embodiments of the present disclosure can be practiced without some of the details described below.
[0013]
[0032] The embodiments described herein are described below with reference to roll-to-roll coating systems, such as the TopMet® roll-to-roll web coating system, the SMARTWEB® roll-to-roll web coating system, and the TOPBEAM® roll-to-roll web coating system, all of which are available from Applied Materials, Inc., Santa Clara, Calif. Other tools capable of performing high-speed deposition processes may also be adapted to benefit from the embodiments described herein. In addition, any system that enables the deposition processes described herein may be advantageously used. The apparatus descriptions described herein are exemplary and should not be construed or understood as limiting the scope of the embodiments described herein. Although described as a roll-to-roll process, it should also be understood that the embodiments described herein may also be performed on individual substrates.
[0014]
[0033] The development of rechargeable lithium metal batteries is considered a promising technology that can enable high energy density systems for energy storage. However, current lithium metal batteries suffer from dendrite growth, which has hindered the practical use of lithium metal batteries in portable electronics and electric vehicles. Over the course of several charge-discharge cycles, fine fibers of lithium, called dendrites, form on the lithium metal surface and spread until they come into contact with the other electrode. Passing a current through these dendrites can short-circuit the battery. One of the most challenging aspects of enabling lithium metal battery technology is the development of a stable and efficient solid electrolyte interface (SEI). A stable and efficient SEI provides an effective strategy to suppress dendrite growth and thus achieve improved cycle numbers.
[0015]
[0034] Current SEI films are typically formed in situ during the cell formation cycle process, which generally occurs immediately after cell fabrication. During the cell formation cycle process, where a suitable potential is established at the anode and a specific organic solvent is used as the electrolyte, the organic solvent is decomposed to form the SEI film on the first charge. With typical liquid electrolytes, at low current densities, mossy lithium deposits have been reported and the lithium growth has been attributed to "bottom growth". At higher current densities, a concentration gradient in the electrolyte causes "tip growth", which has caused the cell to short circuit. Depending on the organic solvent used, the SEI film formed on the anode is typically a mixture of lithium oxide, lithium fluoride, and semicarbonate. Initially, the SEI film is electrically insulating but sufficiently conductive to lithium ions. The SEI prevents electrolyte decomposition after the second charge. The SEI can be considered a three-layer system with two critical interfaces. In traditional electrochemical studies, it is often referred to as the electric double layer. In its simplest form, an anode coated with an SEI undergoes three stages when charged. These three stages include electron transfer between the anode (M) and the SEI (M 0 -ne→M n+ M / SEI ); Cation migration from the anode-SEI interface to the SEI-electrolyte (E) interface (M n+ M / SEI →M n+ SEI / E ); and cation transfer from the SEI to the electrolyte at the SEI / electrolyte interface (E(solv)+M n+ SEI / E →M n+ E(solv)).
[0016]
[0035] The power density and recharge rate of a battery depend on how fast the anode can release and gain charge. This in turn depends on how fast the anode can exchange lithium ions through the SEI with the electrolyte. Lithium ion exchange at the SEI is a multi-step process, and like most multi-step processes, the rate of the overall process depends on the slowest step. Studies have shown that anion transport is the bottleneck for most systems. In addition, it is believed that the diffusion properties of the solvent determine the rate of transport between the anode-SEI interface and the SEI-electrolyte (E) interface. Therefore, the best solvents have little mass to maximize the diffusion rate.
[0017]
[0036] Although the specific properties and reactions occurring at the SEI are not fully understood, it is believed that these properties and reactions have a significant impact on the cycling number and capacity of the anode electrode structure. Furthermore, it is believed that the SEI thickens with cycling, which may slow the diffusion of insoluble Li from the electrode / SEI interface to the SEI / electrolyte. For example, at high temperatures, alkyl carbonates in the electrolyte may cause the insoluble Li 2 CO 3 The lithium metal decomposes into anode and lithium ions, which can increase the thickness of the SEI film and clog the pores in the SEI film, restricting the access of lithium ions to the anode. SEI growth can also occur due to gassing at the cathode and particle migration towards the anode. This increases impedance and reduces capacity. Additionally, the randomness of the metallic lithium embedded in the anode during intercalation leads to the formation of dendrites. Over time, the dendrites can puncture the separator and cause short circuits, leading to heat, fire, and / or explosion.
[0018]
[0037] Embodiments of the present disclosure relate to the ex-situ creation of a stable and efficient SEI film that is formed within an energy storage device during its manufacture. This novel and efficient SEI film is believed to suppress lithium dendrite growth and thus achieve superior lithium metal cycling performance compared to current lithium-based anodes that rely on in-situ SEI films.
[0019]
[0038] FIG. 1 illustrates a cross-sectional view of one embodiment of an energy storage device 100 incorporating an anode electrode structure having an SEI film stack 140 formed according to embodiments described herein. In some embodiments, the energy storage device 100 is a rechargeable battery cell. In some embodiments, the energy storage device 100 is combined with other cells to form a rechargeable battery. The energy storage device 100 has a cathode current collector 110, a cathode film 120, a separator film 130, an SEI film stack 140, an anode film 150, and an anode current collector 160. Note that in FIG. 1, the current collector and separator are shown as extending beyond the stack, but the current collector need not extend beyond the stack, and the portion that extends beyond the stack may be used as a tab. The SEI film stack 140 may be formed of more than one layer, such as lithium carbonate (Li 2 CO 3 ), lithium oxide (Li 2 O), lithium nitride (Li 3 N), and chalcogenide films (e.g., CuS, Cu 2 Se, Cu 2 S, Cu 2 Te, CuTe, Bi 2 Te 3 , or Bi 2 Se 3 The membrane may be formed of a fluorine-containing material.
[0020]
[0039] In one embodiment, a portion of the SEI film stack 140 is a lithium film formed of SF 6The LiF portion and the Li 2 It is formed by forming S moieties on the surface of the lithium film. SF 6 The gas can be thermally activated to react with exposed lithium surfaces, or SF 6 The gas can be plasma activated. The thickness of the SEI film stack 140 is 6 This can be controlled by adjusting the gas exposure time and temperature.
[0021]
[0040] The current collectors 110, 160 on the cathode film 120 and the anode film 150 may be the same or different conductors. Examples of metals from which the current collectors 110, 160 may be made include aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), tin (Sn), silicon (Si), manganese (Mn), magnesium (Mg), alloys thereof, and combinations thereof. In one embodiment, at least one of the current collectors 110, 160 is perforated. Furthermore, the current collectors may be of any form factor (e.g., metal foil, sheet, or plate), shape, and micro / macro structure. In one embodiment, at least one of the current collectors 110, 160 comprises a polyethylene terephthalate ("PET") film coated with a metallic material. In one embodiment, the anode current collector 160 is a PET film coated with copper. In another embodiment, the anode current collector 160 is a multi-metal layer on PET. The multi-metal layer may be a combination of copper, chromium, nickel, etc. In one embodiment, the anode current collector 160 is a multi-layer structure including a copper-nickel clad material. In one embodiment, the multi-layer structure includes a first layer of nickel or chromium, a second layer of copper formed on the first layer, and a third layer including nickel, chromium, or both formed on the second layer. In one embodiment, the anode current collector 160 is nickel-coated copper. Additionally, the current collector may be any form factor (e.g., metal foil, sheet, or plate), shape, and micro / macro structure. Generally, in prismatic cells, the tabs are formed of the same material as the current collectors and may be formed during stack fabrication or added later. All components except current collectors 110 and 160 include the lithium-ion electrolyte. In one embodiment, the cathode current collector 110 is aluminum. In one embodiment, cathode current collector 110 has a thickness of about 0.5 μm to about 20 μm (eg, about 1 μm to about 10 μm, about 5 μm to about 10 μm). In one embodiment, anode current collector 160 is copper.In one embodiment, anode current collector 160 has a thickness of about 0.5 μm to about 20 μm (eg, about 1 μm to about 10 μm, about 2 μm to about 8 μm, about 5 μm to about 10 μm).
[0022]
[0041] The anode film 150 or anode may be any material compatible with the cathode film 120 or cathode. The anode film 150 may have an energy capacity of 372 mAh / g or greater, preferably ≧700 mAh / g, and most preferably ≧1000 mAh / g. The anode film 150 may be made of lithium metal, lithium metal foil or lithium alloy foil (e.g., lithium aluminum alloy), or a mixture of materials such as lithium metal and / or lithium alloy and carbon (e.g., coke, graphite), nickel, copper, tin, indium, silicon, oxides thereof, or combinations thereof. The anode film 150 typically includes an intercalation compound containing lithium or an insertion compound containing lithium. In some embodiments in which the anode film 150 includes lithium metal, the lithium metal may be deposited using the methods described herein. The anode film may be formed by physical or chemical thin film techniques such as extrusion, sputtering, electron beam evaporation, chemical vapor deposition (CVD), three-dimensional printing, lithium powder deposition, and the like. In one embodiment, anode film 150 has a thickness of about 0.5 μm to about 20 μm (eg, about 1 μm to about 10 μm, about 5 μm to about 10 μm). In one embodiment, anode film 150 is a lithium metal or lithium metal alloy film.
[0023]
[0042] The SEI membrane stack 140 is formed ex situ on the anode membrane 150. The SEI membrane stack 140 is electrically insulating but sufficiently conductive to lithium ions. In one embodiment, the SEI membrane stack 140 is a non-porous membrane. In another embodiment, the SEI membrane stack 140 is a porous membrane. In one embodiment, the SEI membrane stack 140 has a plurality of nanopores sized to have an average pore size or diameter less than about 10 nanometers (e.g., about 1 nanometer to about 10 nanometers, about 3 nanometers to about 5 nanometers). In another embodiment, the SEI membrane stack 140 has a plurality of nanopores sized to have an average pore size or diameter less than about 5 nanometers. In one embodiment, the SEI membrane stack 140 has a plurality of nanopores having a diameter in the range of about 1 nanometer to about 20 nanometers (e.g., about 2 nanometers to about 15 nanometers, or about 5 nanometers to about 10 nanometers).
[0024]
[0043] The SEI film stack 140 may be a coating or individual layers having a thickness in the range of 1 nanometer to 200 nanometers (e.g., in the range of 5 nanometers to 200 nanometers, in the range of 10 nanometers to 50 nanometers). Without being bound by theory, it is believed that an SEI film greater than 200 nanometers may increase resistance in a rechargeable battery.
[0025]
[0044] Examples of materials that can be included in the SEI film stack 140 include chalcogenide films (e.g., CuS, Cu 2 Se, Cu 2 S, Cu 2 Te, CuTe, Bi 2 Te 3 , or Bi 2 Se 3 membrane) or optionally, lithium carbonate (Li 2 CO 3 ) film, lithium oxide (Li 2 O) film, lithium nitride film (Li 3In one embodiment, the SEI film stack 140 includes a chalcogenide film (e.g., CuS, CuN), and a composite chalcogenide film in combination with at least one of a lithium halide film (e.g., LiF, LiCl, LiBr, or LiI). 2 Se, Cu 2 S, Cu 2 Te, CuTe, Bi 2 Te 3 , or Bi 2 Se 3 Without being bound by theory, it is believed that the SEI film stack 140 can incorporate a Li conductive electrolyte to form a gel during device fabrication, which is beneficial for forming a good solid electrolyte interface (SEI) and also helps to lower resistance. Suitable methods for depositing a portion of the SEI film stack 140 directly onto the lithium metal film include, but are not limited to, physical vapor deposition (PVD), such as evaporation or sputtering, a slot-die process, a thin film transfer process, or a three-dimensional lithium printing process. The portion of the SEI film stack may be formed by plasma treatment of a previously deposited layer (e.g., oxygen plasma treatment of exposed lithium surfaces to form a lithium oxide film).
[0026]
[0045] The cathode membrane 120, or cathode, may be any material compatible with the anode and may include an intercalation compound, an insertion compound, or an electrochemically active polymer. Suitable intercalation materials include, for example, lithium-containing metal oxides, MoS 2 , FeS 2 , MnO 2 , TiS 2 , NbSe 3 , LiCoO 2 , LiNiO 2 , LiMnO 2 , LiMn 2 O 4 , V 6 O 13 , and V 2 O 5Suitable polymers include, for example, polyacetylene, polypyrrole, polyaniline, and polythiophene. The cathode film 120 or cathode may be made from a layered oxide, such as lithium cobalt oxide, an olivine, such as lithium iron phosphate, or a spinel, such as lithium manganese oxide. Exemplary lithium-containing oxides are layered, e.g., lithium cobalt oxide (LiCoO 2 ), or mixed metal oxides, e.g., LiNi x Co 1-2x MnO 2 , LiNiMnCoO 2 ("NMC"), LiNi 0.5 Mn 1.5 O 4 , Li(Ni 0.8 Co 0.15 Al 0.05 )O 2 , LiMn 2 O 4 , and doped lithium-rich layered materials, where x is zero or a non-zero number. An exemplary phosphate is fayalite (LiFePO 4 ), and its variants (e.g., LiFe (1-x) Mg x PO 4 (where x is between 0 and 1), LiMoPO 4 , LiCoPO 4 , LiNiPO 4 , Li 3 V 2 (PO 4 ) 3 , LiVOPO 4 , LiMP 2 O 7 , or Life 1.5 P 2 O 7 where x is zero or a non-zero number. An exemplary fluorophosphate is LiVPO 4 F, LiAlPO 4 F, Li 5 V(PO 4 ) 2 F 2 , Li 5 Cr(PO 4 )2 F 2 , Li 2 CoPO 4 F, or Li 2 NiPO 4 F. An exemplary silicate is Li 2 FeSiO 4 , Li 2 MnSiO 4 , or Li 2 VOSiO 4 An exemplary non-lithium compound is Na 5 V 2 (PO 4 ) 2 F 3 The cathode film 120 can be formed by physical or chemical thin film techniques, such as sputtering, electron beam evaporation, or chemical vapor deposition (CVD). In one embodiment, the cathode film 120 has a thickness of about 10 μm to about 100 μm (e.g., about 30 μm to about 80 μm, or about 40 μm to about 60 μm). In one embodiment, the cathode film 120 is LiCoO 2 In another embodiment, the cathode membrane 120 is an NMC membrane.
[0027]
[0046] The separator membrane 130 comprises a porous (e.g., microporous) polymeric substrate (e.g., separator membrane) capable of conducting ions through the pores. In some embodiments, the porous polymeric substrate itself need not be ionically conductive, but when filled with an electrolyte (liquid, gel, solid, combination, etc.), the combination of the porous substrate and electrolyte is ionically conductive. In one embodiment, the porous polymeric substrate is a multi-layer polymeric substrate. In one embodiment, the pores are micropores. In some embodiments, the porous polymer substrate comprises any commercially available polymeric microporous membrane (e.g., single layer or multilayer), such as products manufactured by Polypore (Celgard Inc. of Charlotte, North Carolina), Toray Tonen (Battery separator film (BSF)), SK Energy (Li-ion battery separator (LiBS)), Evonik Industries (SEPARION® ceramic separator membrane), Asahi Kasei (Hipore™ polyolefin flat film membrane), DuPont (Energain®), and the like. In some embodiments, the porous polymer substrate has a porosity in the range of 20-80% (e.g., in the range of 28-60%). In some embodiments, the porous polymer substrate has an average pore size in the range of 0.02-5 microns (e.g., 0.08-2 microns). In some embodiments, the porous polymer substrate has a Gurley number in the range of 15 to 150 seconds (Gurley number refers to the time it takes for 10 cc of air at 12.2 inches of water to pass through a 1 square inch membrane). In some embodiments, the porous polymer substrate is polyolefin-based. Exemplary polyolefins include polypropylene, polyethylene, or combinations thereof.
[0028]
[0047] In some embodiments of the energy storage device of the present disclosure, lithium is provided in the form of a lithium metal film in the anode electrode and a lithium manganese oxide (LiMnO 4) or lithium cobalt oxide (LiCoO 2 ), but in some embodiments the anode electrode can also include a lithium absorbing material such as silicon, tin, etc. Although the energy storage device is shown as a planar structure, it may be formed into a cylinder by rolling a stack of layers, and further, embodiments of the present disclosure contemplate other cell configurations (e.g., prismatic cells, button cells).
[0029]
[0048] The electrolyte injected into the cell components 120, 130, 140 and 150 can be composed of a liquid / gel or a solid polymer, each of which may be different. In some embodiments, the electrolyte primarily comprises a salt and a medium (e.g., in a liquid electrolyte, the medium may be referred to as a solvent, and in a gel electrolyte, the medium may be a polymer matrix). The salt may be a lithium salt. The lithium salt may be, for example, LiPF 6 , LiAsF 6 , LiCF 3 SO 3 , LiN(CF 3 SO 3 ) 3 , LiBF 6 , and LiClO 4, lithium bistrifluoromethanesulfonimidate (e.g., LiTFSI), BETTE electrolyte (commercially available from 3M Corp. of Minneapolis, Minn.), and combinations thereof. Solvents can include, for example, ethylene carbonate (EC), propylene carbonate (PC), EC / PC, 2-MeTHF (2-methyltetrahydrofuran) / EC / PC, EC / DMC (dimethyl carbonate), EC / DME (dimethylethane), EC / DEC (diethyl carbonate), EC / EMC (ethyl methyl carbonate), EC / EMC / DMC / DEC, EC / EMC / DMC / DEC / PE, PC / DME, and DME / PC. The polymer matrix can include, for example, PVDF (polyvinylidene fluoride), PVDF:THF (PVDF:tetrahydrofuran), PVDF:CTFE (PVDF:chlorotrifluoroethylene) PAN (polyacrylonitrile), and PEO (polyethylene oxide).
[0030]
[0049] 2 illustrates a cross-sectional view of one embodiment of a double-sided anode electrode structure 200 having solid electrolyte interface (SEI) film stacks 240a, 240b (collectively 240) formed according to embodiments described herein. The SEI film stacks 240a, 240b may be used in place of the SEI film stack 140 shown in FIG. 1. Each SEI film stack 240a, 240b includes a chalcogenide film 210a, 210b (collectively 210) formed on a respective anode film 150a, 150b, respectively. The chalcogenide film may be a copper chalcogenide (e.g., CuS, Cu 2 Se, Cu 2 S, Cu 2 Te, CuTe), bismuth chalcogenides (e.g., Bi 2 Te 3 , Bi 2 Se 3 ), and combinations thereof.
[0031]
[0050] 3 illustrates a cross-sectional view of another embodiment of a double-sided anode electrode structure 300 having solid electrolyte interface (SEI) film stacks 340a, 340b (collectively 340) formed according to embodiments described herein. The SEI film stacks 340a, 340b may be used in place of the SEI film stack 140 shown in FIG. 1. Each SEI film stack 340a, 340b includes a chalcogenide film 210a, 210b (collectively 210) formed on a respective anode film 150a, 150b, respectively. The chalcogenide film may be a copper chalcogenide (e.g., CuS, Cu 2 Se, Cu 2 S, Cu 2 Te, CuTe), bismuth chalcogenides (e.g., Bi 2 Te 3 , Bi 2 Se 3 Each SEI film stack 340a, 340b is selected from the group consisting of a Li SiO 2 film formed on a chalcogenide film 210a, 210b (collectively 210). 2 Each SEI film stack 340a, 340b further includes a LiO film 310a, 310b (collectively 310). 2 Li formed on O films 310a and 310b (collectively 310) 2 CO 3 It further includes membranes 320a, 320b (collectively 320).
[0032]
[0051] 4 illustrates a cross-sectional view of another embodiment of a double-sided anode electrode structure 400 having solid electrolyte interface (SEI) film stacks 440a, 440b (collectively 440) formed according to embodiments described herein. The SEI film stacks 440a, 440b can be used in place of the SEI film stack 140 shown in FIG. 1. Each SEI film stack 440a, 440b includes a Li-type anode electrode 400 formed on each anode film 150a, 150b, respectively. 2 Each SEI film stack 440a, 440b includes a LiO film 310a, 310b (collectively 310). 2 Li formed on O films 310a and 310b (collectively 310) 2 CO 3Each SEI film stack 440a, 440b further includes a Li 2 CO 3 It further includes chalcogenide films 210a, 210b (collectively 210) formed on films 320a, 320b (collectively 310).
[0033]
[0052] 5 illustrates a cross-sectional view of another embodiment of a double-sided anode electrode structure 500 having solid electrolyte interface (SEI) film stacks 540a, 540b (collectively 540) formed according to embodiments described herein. The SEI film stacks 540a, 540b can be used in place of the SEI film stack 140 shown in FIG. 1. Each SEI film stack 540a, 540b includes a lithium nitride (LiN) film stack 540b formed on each anode film 150a, 150b, respectively. 3 Each SEI film stack 540a, 540b includes a LiN film 510a, 510b (collectively 510) formed on each lithium nitride film 510a, 510b, respectively. 2 Each SEI film stack 540a, 540b further includes a LiO film 310a, 310b (collectively 310). 2 Li formed on O films 310a and 310b (collectively 310) 2 CO 3 Each SEI film stack 540a, 540b further includes a Li 2 CO 3 It further includes chalcogenide films 210a, 210b (collectively 210) formed on films 320a, 320b (collectively 310).
[0034]
[0053] 6 illustrates a cross-sectional view of one embodiment of a double-sided anode electrode structure 600 having solid electrolyte interface (SEI) film stacks 640a, 640b (collectively 640) formed according to embodiments described herein. The SEI film stacks 640a, 640b may be used in place of the SEI film stack 140 shown in FIG. 1. Each SEI film stack 640a, 640b includes a chalcogenide film 210a, 210b (collectively 210) formed on a respective anode film 150a, 150b, respectively. The chalcogenide film may be a copper chalcogenide (e.g., CuS, Cu 2 Se, Cu 2 S, Cu 2 Te, CuTe), bismuth chalcogenides (e.g., Bi 2 Te 3 , Bi 2 Se 3 ), and combinations thereof. Each SEI film stack 640a, 640b further includes a lithium halide film 610a, 610b (collectively 610) formed on the chalcogenide film 210a, 210b (collectively 210). In one embodiment, the lithium halide film is selected from LiF, LiCl, LiBr, and LiI.
[0035]
[0054] It should be noted that although in Figures 2-6 the anode current collector 160 is shown as extending beyond the stack, the anode current collector 160 need not extend beyond the stack and the portion that extends beyond the stack may be used as a tab. Although the anode electrode structure shown in Figures 2-6 is depicted as a double-sided electrode structure, it should be understood that the embodiments described in Figures 2-6 also apply to single-sided electrode structures.
[0036]
[0055] FIG. 7 shows a process flow diagram summarizing one embodiment of a method 700 for forming an anode electrode structure having a solid electrolyte interface (SEI) film stack according to embodiments described herein. In one embodiment, the anode electrode structure is a double-sided anode electrode structure 200 as shown in FIG. 2. In another embodiment, the anode electrode structure is a double-sided anode electrode structure 300 as shown in FIG. 3. In step 710, a substrate is provided. In one embodiment, the substrate is a continuous sheet of material 1150 as shown in FIG. 11. In one embodiment, the substrate is an anode current collector 160. Examples of metals that can comprise the substrate include aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), stainless steel, clad materials, alloys thereof, and combinations thereof. In one embodiment, the substrate is a copper material. In one embodiment, the substrate is perforated. Additionally, the substrate may be of any form factor (e.g., metal foil, sheet, or plate), shape, and micro / macro structure.
[0037]
[0056] In some embodiments, the substrate is exposed to a pretreatment process comprising at least one of a plasma treatment or a corona discharge process to remove organic material from the exposed surface of the current collector, the pretreatment process being performed prior to film deposition on the substrate.
[0038]
[0057] In step 720, a lithium metal film is formed on the substrate. In one embodiment, the lithium metal film is an anode film 150 and the substrate is an anode current collector 160. In one embodiment, the lithium metal film is formed on a copper current collector. In some embodiments, if an anode film is already present on the substrate, the lithium metal film is formed on the anode film. If the anode film 150 is not present, the lithium metal film may be formed directly on the substrate. The lithium metal film can be deposited using any suitable lithium metal film deposition process for depositing a thin film of lithium metal. The deposition of the thin film of lithium metal can be by evaporation, a PVD process such as a sputtering process, a slot die process, a transfer process, or a three-dimensional lithium printing process. The chamber for depositing the thin film of lithium metal can include a PVD system such as an electron beam evaporator, a thermal evaporator, or a sputtering system, a thin film transfer system (including a large area pattern printing system such as a gravure printing system), or a slot die deposition system. In one embodiment, the anode membrane 150 has a thickness of 100 micrometers or less (eg, about 1 μm to about 100 μm, about 3 μm to about 30 μm, about 20 μm to about 30 μm, about 1 μm to about 20 μm, or about 50 μm to about 100 μm).
[0039]
[0058] In step 730, an SEI film stack is formed on the lithium metal film. The SEI film stack may be a chalcogenide film (e.g., CuS, Cu 2 Se, Cu 2 S, Cu 2 Te, CuTe, Bi 2 Te 3 , or Bi 2 Se 3 membrane), and optionally lithium carbonate (Li 2 CO 3 ) film and lithium oxide (Li 2 In one embodiment, the SEI film stack includes a chalcogenide film (e.g., CuS, CuO) similar to the SEI film stack 240 shown in FIG. 2 Se, Cu 2 S, Cu2 Te, CuTe, Bi 2 Te 3 , or Bi 2 Se 3 In another embodiment, the SEI film stack includes only a chalcogenide film (e.g., CuS ... 2 Se, Cu 2 S, Cu 2 Te, CuTe, Bi 2 Te 3 , or Bi 2 Se 3 film), a lithium oxide film formed on a chalcogenide film, and a lithium carbonate film formed on a lithium oxide film.
[0040]
[0059] At step 740, a chalcogenide film is formed on the lithium metal film. In one embodiment, the chalcogenide film is Bi 2 Te 3In one embodiment, the chalcogenide film is the chalcogenide film 210 shown in FIG. 2-FIG. 6. In one embodiment, the chalcogenide film has a thickness of 500 nanometers or less (e.g., about 1 nm to about 400 nm, about 25 nm to about 300 nm, about 50 nm to about 200 nm, about 100 nm to about 150 nm, about 10 nm to about 80 nm, or about 30 to about 60 nanometers). In one embodiment, the chalcogenide film is deposited using a PVD process having an RF power source coupled to a target. The target is typically composed of the material of the chalcogenide film. In one embodiment, the target is a bismuth telluride alloy target. In one embodiment, the bismuth telluride alloy target includes about 5 atomic % to about 95 atomic % bismuth and about 5 atomic % to about 95 atomic % tellurium. A plasma can be generated from a non-reactive gas such as argon (Ar), krypton (Kr), or nitrogen. For example, the plasma can be generated from argon gas having a flow rate in the range of about 30 standard cubic centimeters (sccm) to about 200 sccm, such as about 100 sccm to about 150 sccm. RF power can be applied to the target at a power level in the range of about 50 W to about 4,000 W, such as about 1000 W to about 3000 W, such as about 2000 W. The deposition chamber can be pressurized to about 0.1 mTorr to about 500 mTorr. The deposition chamber can be pressurized to about 0.1 mTorr to about 100 mTorr, such as about 10 mTorr to about 30 mTorr, such as about 25 mTorr. The substrate can be electrically "floating" and can have no bias. The deposition process of step 740 can be performed at a deposition temperature of about 50° C. to about 400° C., such as about 100° C. to about 200° C., such as about 120° C.
[0041]
[0060] In another embodiment, the plasma may be generated using a DC power source coupled to a bismuth telluride alloy target. The substrate may be electrically "floating" and may have no bias. In this embodiment, the plasma may be generated from argon gas having a flow rate in the range of about 30 standard cubic centimeters (sccm) to about 200 sccm, such as about 100 sccm to about 150 sccm. DC power may be applied to the target at a power level in the range of about 50 W to about 5,000 W, such as about 1000 W to about 3000 W, such as about 1000 W to about 2000 W, such as about 2000 W. The deposition chamber may be pressurized to about 0.1 mTorr to about 500 mTorr. The deposition chamber may be pressurized to about 0.1 mTorr to about 500 mTorr. The deposition chamber may be pressurized to about 0.1 mTorr to about 100 mTorr, such as about 10 mTorr to about 30 mTorr, such as 25 mTorr. The substrate may be electrically "floating" and may have no bias. The deposition process of step 740 may be carried out at a deposition temperature between about 50°C and about 400°C, such as between about 100°C and about 200°C, for example about 120°C.
[0042]
[0061] Optionally, in step 750, lithium oxide (Li 2A lithium oxide (O) film is formed on the chalcogenide film. In one embodiment, the lithium oxide film is lithium oxide film 310 shown in FIGS. 2-6. In one embodiment, the lithium oxide film has a thickness of 500 nanometers or less (e.g., about 1 nm to about 4000 nm, about 25 nm to about 300 nm, about 50 nm to about 200 nm, or about 100 nm to about 150 nm). In one embodiment, the lithium oxide film is formed by depositing an additional lithium metal film on the chalcogenide film and exposing the lithium metal film to a plasma oxidation process to oxidize the lithium metal film. In one embodiment, the lithium oxide film is formed by depositing an additional lithium metal film by PVD in an oxygen-containing atmosphere. In one embodiment, a portion of the lithium metal film deposited during step 720 remains exposed after deposition of the chalcogenide film in step 740. The exposed portion of the lithium metal film is then exposed to a plasma oxidation process to form a lithium oxide film.
[0043]
[0062] Optionally, in step 760, lithium carbonate (Li 2 CO 3 ) film is formed on the lithium oxide film. In one embodiment, the lithium carbonate film is lithium carbonate film 320 shown in Figures 3-5. In one embodiment, the lithium carbonate film has a thickness of 500 nanometers or less (e.g., about 1 nm to about 400 nm, about 25 nm to about 300 nm, about 50 nm to about 200 nm, or about 100 nm to about 150 nm). In one embodiment, the lithium carbonate film is formed by depositing an additional lithium metal film on the lithium oxide film and oxidizing the lithium metal film using a plasma oxidation process (e.g., O 2 and CO 2 In one embodiment, the lithium oxide film is formed by oxidizing the lithium metal film by exposing it to an oxygen-containing atmosphere (e.g., O 2 and CO 2 In one embodiment, a portion of the lithium oxide film deposited during step 750 is exposed to a plasma oxidation process to form a lithium carbonate film.
[0044]
[0063] FIG. 8 shows a process flow diagram summarizing one embodiment of another method 800 for forming an anode electrode structure having a solid electrolyte interface (SEI) film stack according to embodiments described herein. In one embodiment, the anode electrode structure is a double-sided anode electrode structure 400 as shown in FIG. 4. In another embodiment, the anode electrode structure is a double-sided anode electrode structure 500 as shown in FIG. 5. In step 810, a substrate is provided. In one embodiment, the substrate is a continuous sheet of material 1150 as shown in FIG. 11. In one embodiment, the substrate is an anode current collector 160. Examples of metals that can comprise the substrate include aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), stainless steel, clad materials, alloys thereof, and combinations thereof. In one embodiment, the substrate is a copper material. In one embodiment, the substrate is perforated. Additionally, the substrate may be of any form factor (e.g., metal foil, sheet, or plate), shape, and micro / macro structure.
[0045]
[0064] In some embodiments, the substrate is exposed to a pretreatment process comprising at least one of a plasma treatment or a corona discharge process to remove organic material from the exposed surface of the current collector, the pretreatment process being performed prior to film deposition on the substrate.
[0046]
[0065] In step 820, a lithium metal film is formed on the substrate. In one embodiment, the lithium metal film is an anode film 150 and the substrate is an anode current collector 160. In one embodiment, the lithium metal film is formed on a copper current collector. In some embodiments, if an anode film is already present on the substrate, the lithium metal film is formed on the anode film. If the anode film 150 is not present, the lithium metal film may be formed directly on the substrate. The lithium metal film can be deposited using any suitable lithium metal film deposition process for depositing a thin film of lithium metal. The deposition of the thin film of lithium metal can be by evaporation, a PVD process such as a sputtering process, a slot die process, a transfer process, or a three-dimensional lithium printing process. The chamber for depositing the thin film of lithium metal can include a PVD system such as an electron beam evaporator, a thermal evaporator, or a sputtering system, a thin film transfer system (including a large area pattern printing system such as a gravure printing system), or a slot die deposition system. In one embodiment, the anode membrane 150 has a thickness of 100 micrometers or less (eg, about 1 μm to about 100 μm, about 3 μm to about 30 μm, about 20 μm to about 30 μm, about 1 μm to about 20 μm, or about 50 μm to about 100 μm).
[0047]
[0066] In step 830, an SEI film stack is formed on the lithium metal film. The SEI film stack is made of lithium oxide (Li 2 O) film, lithium carbonate (Li 2 CO 3 ) films, chalcogenide films (e.g., CuS, Cu 2 Se, Cu 2 S, Cu 2 Te, CuTe, Bi 2 Te 3 , or Bi 2 Se 3 film), and optionally lithium nitride (Li 3 In one embodiment, the SEI film stack includes a lithium nitride (LiN) film formed on a lithium metal film, similar to the SEI film stack 540 shown in FIG. 3N) film, lithium oxide (Li) formed on lithium nitride film 2 O) film, lithium carbonate (Li 2 CO 3 ) film, and chalcogenide films (e.g., Bi 2 Te 3 In another embodiment, the SEI film stack includes a lithium oxide (Li ) formed on a lithium metal film, similar to the SEI film stack 440 shown in FIG. 2 O) film, lithium carbonate (Li 2 CO 3 ) film, and chalcogenide films (e.g., CuS, Cu 2 Se, Cu 2 S, Cu 2 Te, CuTe, Bi 2 Te 3 , or Bi 2 Se 3 membrane).
[0048]
[0067] Optionally, in step 840, lithium nitride (Li 3 A lithium nitride film is formed on the lithium metal film. In one embodiment, the lithium nitride film is lithium nitride film 510 shown in FIG. 5. In one embodiment, the lithium nitride film has a thickness of 500 nanometers or less (e.g., about 1 nm to about 400 nm, about 25 nm to about 300 nm, about 50 nm to about 200 nm, or about 1 nm to about 50 nm). In one embodiment, the lithium nitride film is formed by depositing an additional lithium metal film on the lithium metal film and exposing the lithium metal film to a plasma nitridation process to form the lithium nitride film. In one embodiment, the lithium nitride film is formed by depositing the additional lithium metal film by PVD in a nitrogen-containing atmosphere.
[0049]
[0068] In step 850, lithium oxide (Li 2O) film is formed. If a lithium nitride film is present, a lithium oxide film is formed on the lithium nitride film. If lithium nitride is not present, a lithium oxide film is formed on the lithium metal film. In one embodiment, the lithium oxide film is the lithium oxide film 310 shown in Figures 4-5. In one embodiment, the lithium oxide film has a thickness of 500 nanometers or less (e.g., about 1 nm to about 4000 nm, about 25 nm to about 300 nm, about 50 nm to about 200 nm, or about 100 nm to about 150 nm). In one embodiment, the lithium oxide film is formed by depositing an additional lithium metal film on the lithium nitride film and exposing the lithium metal film to a plasma oxidation process to oxidize the lithium metal film. In one embodiment, the lithium oxide film is formed by depositing an additional lithium metal film by PVD in an oxygen-containing atmosphere. In one embodiment, the lithium nitride film is exposed to a plasma oxidation process to form a lithium oxide film. In one embodiment where a lithium nitride film is not present, the lithium metal film deposited during step 820 is exposed to a plasma oxidation process to form a lithium oxide film.
[0050]
[0069] In step 860, lithium carbonate (Li 2 CO 3 ) film is formed on the lithium oxide film. In one embodiment, the lithium carbonate film is lithium carbonate film 320 shown in Figures 4-5. In one embodiment, the lithium carbonate film has a thickness of 500 nanometers or less (e.g., about 1 nm to about 400 nm, about 25 nm to about 300 nm, about 50 nm to about 200 nm, or about 100 nm to about 150 nm). In one embodiment, the lithium carbonate film is formed by depositing an additional lithium metal film on the lithium oxide film and oxidizing the lithium metal film using a plasma oxidation process (e.g., O 2 and CO 2 In one embodiment, the lithium oxide film is formed by oxidizing the lithium metal film by exposing it to an oxygen-containing atmosphere (e.g., O 2 and CO 2In one embodiment, a portion of the lithium oxide film deposited during step 750 is exposed to a plasma oxidation process to form a lithium carbonate film.
[0051]
[0070] At step 870, a chalcogenide film is formed on the lithium carbonate film. In one embodiment, the chalcogenide film is Bi 2 Te 3 In one embodiment, the chalcogenide film is chalcogenide film 210 shown in FIGS. 4-5. In one embodiment, the chalcogenide film is deposited using the process conditions described in step 740. In one embodiment, the chalcogenide film has a thickness of 500 nanometers or less (e.g., about 1 nm to about 400 nm, about 25 nm to about 300 nm, about 50 nm to about 200 nm, about 100 nm to about 150 nm, about 10 nm to about 80 nm, or about 30 to about 60 nanometers). The chalcogenide film can be formed using any suitable deposition process. In one embodiment, the chalcogenide film is deposited using the process described in step 740.
[0052]
[0071] FIG. 9 shows a process flow diagram summarizing one embodiment of another method 900 for forming an anode electrode structure with a solid electrolyte interface (SEI) film stack according to embodiments described herein. In one embodiment, the anode electrode structure is a double-sided anode electrode structure 600 as shown in FIG. 6. In step 910, a substrate is provided. In one embodiment, the substrate is a continuous sheet of material 1150 as shown in FIG. 11. In one embodiment, the substrate is an anode current collector 160. Examples of metals that can comprise the substrate include aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), stainless steel, clad materials, alloys thereof, and combinations thereof. In one embodiment, the substrate is a copper material. In one embodiment, the substrate is perforated. Additionally, the substrate may be of any form factor (e.g., metal foil, sheet, or plate), shape, and micro / macro structure.
[0053]
[0072] In some embodiments, the substrate is exposed to a pretreatment process comprising at least one of a plasma treatment or a corona discharge process to remove organic material from the exposed surface of the current collector, the pretreatment process being performed prior to film deposition on the substrate.
[0054]
[0073] In step 920, a lithium metal film is formed on the substrate. In one embodiment, the lithium metal film is an anode film 150 and the substrate is an anode current collector 160. In one embodiment, the lithium metal film is formed on a copper current collector. In some embodiments, if an anode film is already present on the substrate, the lithium metal film is formed on the anode film. If the anode film 150 is not present, the lithium metal film may be formed directly on the substrate. The lithium metal film can be deposited using any suitable lithium metal film deposition process for depositing a thin film of lithium metal. The deposition of the thin film of lithium metal can be by evaporation, a PVD process such as a sputtering process, a slot die process, a transfer process, or a three-dimensional lithium printing process. The chamber for depositing the thin film of lithium metal can include a PVD system such as an electron beam evaporator, a thermal evaporator, or a sputtering system, a thin film transfer system (including a large area pattern printing system such as a gravure printing system), or a slot die deposition system. In one embodiment, the anode membrane 150 has a thickness of 100 micrometers or less (eg, about 1 μm to about 100 μm, about 3 μm to about 30 μm, about 20 μm to about 30 μm, about 1 μm to about 20 μm, or about 50 μm to about 100 μm).
[0055]
[0074] In step 930, an SEI film stack is formed on the lithium metal film. The SEI film stack may be a chalcogenide film (e.g., CuS, Cu 2 Se, Cu 2 S, Cu 2 Te, CuTe, Bi 2 Te 3 , or Bi 2 Se 3 film), where a lithium fluoride (LiF) film is formed over the chalcogenide film, similar to the SEI film stack 640 shown in FIG.
[0056]
[0075] At step 940, a chalcogenide film is formed on the lithium carbonate film. In one embodiment, the chalcogenide film is Bi 2 Te 3In one embodiment, the chalcogenide film is chalcogenide film 210 shown in FIGS. 4-5. In one embodiment, the chalcogenide film is deposited using the process conditions described in step 740. In one embodiment, the chalcogenide film has a thickness of 500 nanometers or less (e.g., about 1 nm to about 400 nm, about 25 nm to about 300 nm, about 50 nm to about 200 nm, about 100 nm to about 150 nm, about 10 nm to about 80 nm, or about 30 to about 60 nanometers). The chalcogenide film can be formed using any suitable deposition process. In one embodiment, the chalcogenide film is deposited using the process described in step 740.
[0057]
[0076] In step 950, a lithium halide film is formed on the chalcogenide film. In one embodiment, the lithium halide film is the lithium halide film 610 shown in FIG. 6. In one embodiment, the lithium halide film is deposited on the chalcogenide film by physical vapor deposition (PVD), such as evaporation or sputtering, specialized atomic layer deposition (ALD), a slot-die process, a thin film transfer process, or a three-dimensional lithium printing process. In one embodiment, PVD is the deposition method for the lithium fluoride film. In one embodiment, the lithium halide film is selected from LiF, LiCl, LiBr, and LiI. In one embodiment, the lithium halide film is a lithium fluoride film. In one embodiment, the lithium halide film is deposited using a thermal evaporation process. In one embodiment, the lithium fluoride film has a thickness of 500 nanometers or less (e.g., about 1 nm to about 400 nm, about 25 nm to about 300 nm, about 50 nm to about 200 nm, or about 100 nm to about 150 nm).
[0058]
[0077] FIG. 10 shows a process flow diagram summarizing one embodiment of another method 1000 for forming an anode electrode structure with a solid electrolyte interface (SEI) film stack according to embodiments described herein. In one embodiment, the anode electrode structure is a double-sided anode electrode structure 600 as shown in FIG. 6. In step 1010, a substrate is provided. In one embodiment, the substrate is a continuous sheet of material 1150 as shown in FIG. 11. In one embodiment, the substrate is an anode current collector 160. Examples of metals that can comprise the substrate include aluminum (Al), copper (Cu), zinc (Zn), nickel (Ni), cobalt (Co), manganese (Mn), chromium (Cr), stainless steel, clad materials, alloys thereof, and combinations thereof. In one embodiment, the substrate is a copper material. In one embodiment, the substrate is perforated. Additionally, the substrate may be of any form factor (e.g., metal foil, sheet, or plate), shape, and micro / macro structure.
[0059]
[0078] In some embodiments, the substrate is exposed to a pretreatment process comprising at least one of a plasma treatment or a corona discharge process to remove organic material from the exposed surface of the current collector, the pretreatment process being performed prior to film deposition on the substrate.
[0060]
[0079] In step 1020, a lithium metal film is formed on the substrate. In one embodiment, the lithium metal film is an anode film 150 and the substrate is an anode current collector 160. In one embodiment, the lithium metal film is formed on a copper current collector. In some embodiments, if an anode film is already present on the substrate, the lithium metal film is formed on the anode film. If the anode film 150 is not present, the lithium metal film may be formed directly on the substrate. The lithium metal film can be deposited using any suitable lithium metal film deposition process for depositing a thin film of lithium metal. The deposition of the thin film of lithium metal can be by evaporation, a PVD process such as a sputtering process, a slot die process, a transfer process, or a three-dimensional lithium printing process. The chamber for depositing the thin film of lithium metal can include a PVD system such as an electron beam evaporator, a thermal evaporator, or a sputtering system, a thin film transfer system (including a large area pattern printing system such as a gravure printing system), or a slot die deposition system. In one embodiment, the anode membrane 150 has a thickness of 100 micrometers or less (eg, about 1 μm to about 100 μm, about 3 μm to about 30 μm, about 20 μm to about 30 μm, about 1 μm to about 20 μm, or about 50 μm to about 100 μm).
[0061]
[0080] In step 1030, an SEI film stack is formed on the lithium metal film. The SEI film stack includes a composite film of lithium halide and chalcogenide. In one embodiment, the SEI film stack includes a lithium fluoride (LiF) film, a lithium carbonate (Li 2 CO 3 ) film, lithium oxide film, lithium nitride (Li 3 The composite film further comprises at least one of a chalcogenide material (e.g., CuS, CuN) film, a chalcogenide film, and combinations thereof. 2 Se, Cu 2 S, Cu 2 Te, CuTe, Bi 2 Te 3 , or Bi 2 Se 3The lithium fluoride material may be a composite membrane comprising a lithium fluoride material and a lithium halide material (e.g., lithium fluoride).
[0062]
[0081] In step 1040, a lithium halide and chalcogenide composite film is formed on the underlying film (e.g., a lithium metal film). In one embodiment, the lithium halide and chalcogenide composite film is formed of LiF and Bi 2 Te 3 The composite film is a composite film of lithium halide and chalcogenide. In one embodiment, the composite film of lithium halide and chalcogenide is chalcogenide film 210 shown in FIG. 4-FIG. 5. In one embodiment, the composite film of lithium halide and chalcogenide is deposited using the process conditions described in step 740, the process conditions described in step 940, or a combination of the processes of steps 740 and 940. In one embodiment, the composite film of lithium halide and chalcogenide has a thickness of 500 nanometers or less (e.g., about 1 nm to about 400 nm, about 25 nm to about 300 nm, about 50 nm to about 200 nm, about 100 nm to about 150 nm, about 10 nm to about 80 nm, or about 30 to about 60 nanometers). The composite film of lithium halide and chalcogenide can be formed using any suitable deposition process. In one embodiment, the lithium halide and chalcogenide composite film is deposited by physical vapor deposition (PVD), such as evaporation or sputtering, specialized atomic layer deposition (ALD), a slot-die process, a thin film transfer process, a three-dimensional lithium printing process, or a combination thereof. In one embodiment, PVD is the deposition method for the lithium fluoride film.
[0063]
[0082] FIG. 11 shows a schematic diagram of a flexible substrate coating apparatus 1100 for forming an anode electrode structure according to embodiments described herein. The flexible substrate coating apparatus 1100 may be a SMARTWEB® manufactured by Applied Materials adapted to manufacture lithium anode devices according to embodiments described herein. According to an exemplary embodiment, the flexible substrate coating apparatus 1100 can be used to manufacture lithium anodes, in particular for SEI film stacks for lithium anodes. The flexible substrate coating apparatus 1100 is configured as a roll-to-roll system including an unwinding module 1102, a processing module 1104, and a winding module 1106. In some embodiments, the processing module 1104 comprises multiple processing modules or chambers 1110, 1120, 1130, and 1140 arranged in sequence, each configured to perform one processing operation on a continuous sheet of material 1150 or web of material. In one embodiment, as shown in FIG. 11, the processing chambers 1110-1140 are arranged radially around a coating drum 1155. Arrangements other than radial are also contemplated, for example, in another embodiment the processing chambers may be arranged in a linear configuration.
[0064]
[0083] In one embodiment, the processing chambers 1110-1140 are stand-alone modular processing chambers, with each modular processing chamber being structurally isolated from the other modular processing chambers. Thus, each of the stand-alone modular processing chambers can be independently positioned, rearranged, replaced, or serviced without affecting the other. Although four processing chambers 1110-1140 are shown, it should be understood that any number of processing chambers may be included in the flexible substrate coating apparatus 1100.
[0065]
[0084] The processing chambers 1110-1140 may include any suitable structure, configuration, arrangement, and / or components that enable the flexible substrate coating apparatus 1100 to deposit lithium anode devices according to embodiments of the present disclosure. For example, but not limited to, the processing chambers may include a suitable deposition system including a coating source, a power source, individual pressure control devices, a deposition control system, and a temperature control device. According to typical embodiments, the chambers are provided with individual gas supplies. The chambers are typically separated from each other to provide good gas isolation. The flexible substrate coating apparatus 1100 according to embodiments described herein is not limited in the number of deposition chambers. For example, but not limited to, the flexible substrate coating apparatus 1100 may include 3, 6, or 12 processing chambers.
[0066]
[0085] The processing chambers 1110-1140 typically include one or more deposition units 1112, 1122, 1132, and 1142. In general, the one or more deposition units as described herein can be selected from the group of CVD sources, PECVD sources, and PVD sources. The one or more deposition units can include an evaporation source, a sputtering source, for example, a magnetron sputtering source, a DC sputtering source, an AC sputtering source, a pulsed sputtering source, radio frequency (RF) sputtering, or a medium frequency (MF) sputtering. For example, MF sputtering having a frequency in the range of 5 kHz to 100 kHz, for example, 30 kHz to 50 kHz can be included. The one or more deposition units can include an evaporation source. In one embodiment, the evaporation source is a thermal evaporation source or an electron beam evaporation source. In one embodiment, the evaporation source is a lithium (Li) source. The evaporation source can also be an alloy of two or more metals. The material to be deposited (for example, lithium) can be provided in a crucible. The lithium can be deposited, for example, by thermal evaporation or electron beam evaporation techniques.
[0067]
[0086] In some embodiments, any of the processing chambers 1110-1140 of the flexible substrate coating apparatus 1100 may be configured to perform deposition by sputtering, such as magnetron sputtering. As used herein, "magnetron sputtering" refers to sputtering performed using a magnet assembly, i.e., a unit capable of generating a magnetic field. Typically, such a magnet assembly includes a permanent magnet. This permanent magnet is usually disposed within a rotatable target or coupled to a planar target such that free electrons are trapped within the generated magnetic field generated below the rotatable target surface. Such a magnet assembly may also be disposed coupled to a planar cathode.
[0068]
[0087] Magnetron sputtering can also be accomplished with a dual magnetron cathode, such as, but not limited to, the TwinMag™ cathode assembly. In some embodiments, the cathodes in the process chamber may be interchangeable. Thus, a modular design of the apparatus is provided, which facilitates optimization of the apparatus for a particular manufacturing process. In some embodiments, the number of cathodes in the sputtering deposition chamber is selected to optimize the productivity of the flexible substrate coating apparatus 1100.
[0069]
[0088] In some embodiments, one or some of the processing chambers 1110-1140 may be configured to perform sputtering without a magnetron assembly. In some embodiments, one or some of the chambers may be configured to perform deposition by other methods, such as, but not limited to, chemical vapor deposition, atomic laser deposition, or pulsed laser deposition. In some embodiments, one or some of the chambers may be configured to perform a plasma treatment process, such as a plasma oxidation or plasma nitridation process.
[0070]
[0089] In certain embodiments, the processing chambers 1110-1140 are configured to process both sides of the continuous sheet of material 1150. Although the flexible substrate coating apparatus 1100 is configured to process the continuous sheet of material 1150 that is oriented horizontally, the flexible substrate coating apparatus 1100 may be configured to process substrates that are disposed in different orientations, for example, the continuous sheet of material 1150 may be oriented vertically. In certain embodiments, the continuous sheet of material 1150 is a flexible conductive substrate. In certain embodiments, the continuous sheet of material 1150 comprises a conductive substrate having one or more layers formed thereon. In certain embodiments, the conductive substrate is a copper substrate.
[0071]
[0090] In certain embodiments, the flexible substrate coating apparatus 1100 includes a transport mechanism 1152. The transport mechanism 1152 can include any transport mechanism capable of moving a continuous sheet of material 1150 through the processing regions of the processing chambers 1110-1140. The transport mechanism 1152 can include a common transport architecture. The common transport architecture can include a reel-to-reel system having a common take-up reel 1154 disposed in the take-up module 1106, a coating drum 1155 disposed in the processing module 1104, and a supply reel 1156 disposed in the unwind module 1102. The take-up reel 1154, the coating drum 1155, and the supply reel 1156 can be individually heated. The take-up reel 1154, the coating drum 1155, and the supply reel 1156 can be individually heated using an internal or external heat source disposed in each reel. The general transport architecture may further include one or more auxiliary transfer reels 1153a, 1153b disposed between the take-up reel 1154, the coating drum 1155, and the supply reel 1156. Although the flexible substrate coating apparatus 1100 is shown as having a single processing area, in certain embodiments it may be advantageous to have separate or separate processing areas for each individual processing chamber 1110-1140. In embodiments having separate processing areas, modules, or chambers, the general transport architecture may be a reel-to-reel system in which each chamber or processing area has its own take-up reel and supply reel, as well as one or more optional intermediate transfer reels disposed between the take-up reel and the supply reel.
[0072]
[0091] The flexible substrate coating apparatus 1100 may include a supply reel 1156 and a take-up reel 1154 for moving the continuous sheet of material 1150 through the various processing chambers 1110-1140. In one embodiment, the first processing chamber 1110 and the second processing chamber 1120 are each configured to deposit a portion of a lithium metal film. The third processing chamber 1130 is configured to deposit a chalcogenide film. The fourth processing chamber 1140 is configured to deposit a lithium oxide or lithium fluoride film on the chalcogenide film. In another embodiment where the continuous sheet of material 1150 is a polymeric material, the first processing chamber 1110 is configured to deposit a copper film on the polymeric material. The second processing chamber 1120 and the third processing chamber 1130 are each configured to deposit a portion of a lithium metal film. The fourth processing chamber 1140 is configured to deposit a chalcogenide film. In some embodiments, the completed negative electrodes may proceed directly to integration with separators, positive electrodes, etc. to form a battery cell, rather than being collected on a take-up reel 1154 as shown.
[0073]
[0092] In one embodiment, the processing chambers 1110-1120 are configured to deposit a thin film of lithium metal on the continuous sheet of material 1150. The thin film of lithium metal can be deposited using any suitable lithium deposition process for depositing a thin film of lithium metal. The deposition of the thin film of lithium metal may be done by a PVD process such as evaporation, a slot-die process, a transfer process, a lamination process or a three-dimensional lithium printing process. The chamber for depositing the thin film of lithium metal may include a PVD system such as an electron beam evaporator, a thin film transfer system (including a large area pattern printing system such as a gravure printing system), a lamination system, or a slot-die deposition system.
[0074]
[0093] In one embodiment, the third processing chamber 1130 is configured to deposit a chalcogenide film on the lithium metal film. The chalcogenide film can be deposited using a PVD sputtering technique as described herein. In one embodiment, the fourth processing chamber 1140 is configured to form a lithium oxide film or a lithium fluoride film on the chalcogenide film. The lithium metal thin film can be deposited using any suitable lithium deposition process for depositing a thin film of lithium metal. The deposition of the lithium metal thin film may be done by a PVD process such as vapor deposition, a slot die process, a transfer process, a lamination process or a three-dimensional lithium printing process. In one embodiment, the fourth processing chamber 1140 is an evaporation chamber or a PVD chamber configured to deposit a lithium fluoride film or a lithium oxide film on the continuous sheet of material 1150. In one embodiment, the evaporation chamber has a processing region shown with an evaporation source that can be located in a crucible, which can be, for example, a thermal evaporator or an electron beam evaporator (low temperature) in a vacuum environment.
[0075]
[0094] In operation, a continuous sheet of material 1150 is unwound from a supply reel 1156, as indicated by the direction of substrate travel indicated by arrow 1108. The continuous sheet of material 1150 may be guided via one or more auxiliary transfer reels 1153a, 1153b. It is also possible that the continuous sheet of material 1150 is guided by one or more substrate guidance control units (not shown) that control the proper running of the flexible substrate, for example, by fine-tuning the orientation of the flexible substrate.
[0076]
[0095] After being unwound from supply reel 1156 and traveling past auxiliary transfer reel 1153a, the continuous sheet of material 1150 is provided to a coating drum 1155 and moves through deposition zones corresponding to the locations of deposition units 1112, 1122, 1132, and 1142. In operation, the coating drum 1155 rotates about axis 1151 such that the flexible substrate moves in the direction of arrow 1108.
[0077]
[0096] Working Example:
[0078]
[0097] The following non-limiting examples are provided to further illustrate the embodiments described herein, however, these examples are not intended to be comprehensive and are not intended to limit the scope of the embodiments described herein.
[0079]
[0098] The lithium sample is 1.0 cm 2 Disks were cut and prepared and polished with a stainless steel brush in an argon glove box. The lithium was then pressed between polypropylene to obtain a foil with a beautiful metallic luster. The lithium foil, approximately 160 μm thick, was placed on a stainless steel spacer and transferred to the PVD deposition chamber using a transfer container. The target in the PVD deposition chamber was n-type with a composition of 38.6% Bi and 55.1% Te. The PVD deposition chamber was filled with argon and a continuous argon flow of approximately 150 sccm was established. The deposition time was approximately 90 seconds. A process pressure of approximately 25 millitorr was established in the PVD deposition chamber. A deposition temperature of approximately 120 degrees Celsius was established in the PVD deposition chamber. A deposition power of 2 kW (86.5 Å / sec) was used. A spacing of approximately 57 millimeters was established between the target and the lithium sample. Bi 2 Te 3 After completion of the deposition process, the sample was transferred to an argon glove box for further study. 2 Te 3 The thickness of the film varied from about 50 to 200 nanometers. 2 Te 3 Coin cells containing the membranes were assembled and subjected to testing.
[0080]
[0099] 12A to 12D are 0.25 mA / cm 211A and 11B are graphs showing cell voltage change versus time in a symmetric lithium cell (1 hour cycle) at a current density of 1000 mA / cm. The Li / Li symmetric cell study is excellent for investigating the reversibility of the Li anode. FIG. 11A shows the cell configuration for the control cell. The control cell is a Li||Li symmetric cell with bare lithium foil as the electrode, while FIGS. 12B-12D show the cell configuration for the Li||Li symmetric cell with bare lithium foil as the electrode, while FIGS. 12C-12D show the cell configuration for the Li||Li symmetric cell with bare lithium foil as the electrode, while FIGS. 12D-12C show the cell configuration for the Li||Li symmetric cell with bare lithium foil as the electrode, while FIGS. 2 Te 3 Using lithium foil covered with Bi as an electrode 2 Te 3 indicates the protected cell (Li|Bi 2 Te 3 ||Bi 2 Te 3 |Li). 1M LiPF in EC / DEC solvent (volume ratio = 1:1) 6 A standard electrolyte containing 0.250 mA / cm was used. A symmetric cell with the standard electrolyte was assembled as a 2032 coin cell and had a current of 0.250 mA / cm 2 and 3mA / cm 2 As cycling proceeds, lithium plating and stripping continuously alters the surface of the lithium. The newly protected cells are 2 Te 3 It is noted from FIGS. 12A and 12B that the ZnO-based ... CdSe cells exhibited higher impedance due to the insulating nature of the ZnO-based ZnO-based CdSe cells, but after the formation cycle, the impedance was reduced and they outperformed the control cells.
[0081]
[0100] 13A to 13B show the Bi 2 Te 3 1 is a graph of the impedance spectra of a Li / Li symmetric cell with a modified interface and an unmodified lithium control. 2 Te 3 The impedance spectrum of the Li / / Li symmetric cell using the modified interface is shown by trace 1310, and the impedance spectrum of the Li / / Li symmetric cell using the control unmodified lithium is shown by trace 1320. The interfacial resistance shown by trace 1330 is approximately 100% greater than that of the Bi, as shown by trace 1340. 2 Te 3It was dramatically decreased after 300 h of cycling with the modified interface.
[0082]
[0101] FIG. 14 shows a current density of 0.250 mA / cm as indicated by points 1410a-d. 2 and the current density of 3 mA / cm as indicated by points 1420a-d. 2 The control sample vs. the Bi shown in Examples 1 to 3 after 100 hours of polarization at 2 Te 3 1 is a graph showing a comparison of the voltage drop of the modified interface. 2 Te 3 The cell protected with Bi exhibits stable cycling capability for 400 h and low polarization (≈150 mV) at the same current density (FIGS. 12B and 12C). Thus, the superior cycling ability of the protected cell implies homogenous lithium deposits and less lithium and electrolyte consumption in the cell. The stable cycling ability is due to the Bi-protected cell's ability to improve and limit lithium dendrite formation and enhance reversibility. 2 Te 3 Demonstrate the effectiveness of.
[0083]
[0102] FIG. 15A is an SEM image of a lithium control cell. FIG. 2 Te 3 15A and 15B are SEM images of cells protected with 1M LiPF. The morphology of the lithium metal electrode surface from galvanostatic cycling measurements was analyzed by scanning electron microscopy. 6 15A shows the lithium surface after 50 charge-discharge cycles in (EC:DEC 2%FEC). The lithium electrode contact with the control lithium metal formed needle-like nanostructures, as shown in FIG. 15A, while the lithium electrode contact with Bi, as shown in FIG. 15B, 2 Te 3 The lithium surface in contact with the film forms a dense and uniform electrodeposit. These results suggest that the voltage instability and improved stability observed in FIG. 12A are due to the Bi 2 Te 3 We demonstrate that this directly results from the interfacial modification of
[0084]
[0103] 16A-16B show a bare lithium metal anode and a Bi 2 Te 3 1 is a graph showing discharge capacity versus cycle number for a lithium metal anode protected with Bi 2 Te 3 Li / LiCoO with modified Li 2 A CR2032 coin cell was used as a proof platform to test the effectiveness of the anode passivation procedure described herein. The complete cell was constructed using Li metal as the anode, commercially available lithium cobalt oxide as the cathode, and 1M LiPF as the electrolyte. 6 (EC:DEC 2%FEC) was used. 50-100 nm of Bi was deposited on the lithium surface. 2 Te 3 The cell containing 3mA / cm 2 It was observed from FIG. 16A that the Bi provided improved capacity retention for at least 30 charge-discharge cycles at a high current density of 1000 mA. 2 Te 3 The protection of the lithium metal by Bi not only prevents this self-discharge during the rest period before electrochemical cycling begins, but also prevents capacity loss during the first 10 cycles, 2 Te 3 The capacity of the cell using the anode protected by ZnO was negligible, ∼3.5 mAh / cm, as shown in Figure 16B. 2 After 30 cycles, the cells with bare Li metal anodes experienced a more significant loss of their initial capacity, while the cells with protected Li metal anodes experienced only a small loss.
[0085]
[0104] Control and Bi 2 Te 3To evaluate the rate performance of the Bi-coated samples, the electrodes were subjected to charge-discharge cycles at various currents. The discharge capacity values are shown in Figures 17 and 18. Figure 19 is a graph comparing the discharge capacity retention at various discharge rates. Figure 20 is a graph comparing the variation of charge rate capacity versus C-rate. It can be seen that in the comparative example, the discharge capacity retention of the material remains very stable, giving a capacity retention of 95% at 1C discharge rate. To further illustrate, a comparison of the charge capacity retention is plotted. In this example, lithium is deposited on the modified interface. The Bi of the electrode 2 Te 3 The coating has been shown to have a favorable effect on retention, with 80% capacity retention at rates of C / 10, C / 5, C / 2, 1C, and 2C when compared to the control. This is due to the fact that the Bi on Li metal 2 Te 3 The advantages of the coating are further illustrated.
[0086]
[0105] In summary, some embodiments of the present disclosure provide a method for making a stable and efficient SEI film including a chalcogenide material and a device incorporating the SEI film. The SEI film is formed in an energy storage device during the manufacture of the energy storage device (e.g., ex situ). The inventors have found that including a chalcogenide material in the SEI film helps to suppress lithium dendrite growth. Without being bound by theory, it is believed that suppression of lithium dendrite growth helps to achieve superior lithium metal cycling performance compared to current lithium-based anodes that rely on an in situ SEI film that is formed in large part during the first charge of the energy storage device.
[0087]
[0106] When introducing elements of the present disclosure, or exemplary aspects or embodiments thereof, the articles "a," "an," "the," and "said" are intended to mean that there are one or more of the element.
[0088]
[0107] The terms "comprising," "including," and "having" are intended to be inclusive and mean that there may be additional elements other than the listed elements.
[0089]
[0108] While the forgoing is directed to embodiments of the present disclosure, other and further embodiments of the disclosure may be devised without departing from the basic scope of the disclosure, the scope of which is determined by the following claims.
Claims
1. forming a lithium metal film on a current collector including a copper film; forming a chalcogenide film selected from the group consisting of a bismuth chalcogenide film, a copper chalcogenide film, and combinations thereof on the lithium metal film; and forming a lithium halide film on the chalcogenide film; forming a solid electrolyte interface (SEI) film stack on the lithium metal film; The method includes:
2. 2. The method of claim 1, wherein the lithium halide film is selected from lithium fluoride, lithium chloride, lithium bromide, or lithium iodide.
3. The method of claim 2, wherein the chalcogenide film is a bismuth chalcogenide film.
4. The method of claim 2, wherein the chalcogenide film is a copper chalcogenide film.
5. The method of claim 1, wherein the lithium halide film is selected from lithium chloride or lithium bromide.
6. The method of claim 1, further comprising an anode film formed between the current collector and the lithium metal film.
7. The method of claim 1, wherein the lithium metal film is in contact with the copper film.
8. The chalcogenide film is CuS, Cu 2 Se, Cu 2 S, Cu 2 Te, CuTe, Bi 2 Te 3 , Bi 2 Se 3 and combinations thereof.
9. Forming a lithium metal film on a current collector including a copper film; forming a solid electrolyte interface (SEI) film stack on the lithium metal film, the solid electrolyte interface (SEI) film stack including forming a composite film on the lithium metal film; A method comprising: The method, wherein the composite film comprises a lithium halide material and a chalcogenide material, the chalcogenide material being selected from the group of bismuth chalcogenide, copper chalcogenide, and combinations thereof.
10. The method of claim 9, wherein the lithium halide material is selected from lithium fluoride, lithium chloride, lithium bromide or lithium iodide.
11. The method of claim 10, wherein the chalcogenide material is selected from the group consisting of CuS, Cu2Se, Cu2S, Cu2Te, CuTe, Bi2Te3, Bi2Se3, and combinations thereof.
12. The method of claim 10, wherein the chalcogenide material is a bismuth chalcogenide.
13. The method of claim 10, wherein the chalcogenide material is copper chalcogenide.
14. The method of claim 9, further comprising an anode film formed between the current collector and the lithium metal film.
15. The method of claim 9, wherein the lithium metal film is in contact with the copper film.
16. A current collector including a copper film; a lithium metal film formed on the current collector; and a solid electrolyte interface (SEI) film stack formed on the lithium metal film, the SEI film stack including a chalcogenide film formed on the lithium metal film and a lithium halide film on the chalcogenide film; An electrode structure comprising: The electrode structure, wherein the chalcogenide film is selected from the group consisting of bismuth chalcogenide films, copper chalcogenide films, and combinations thereof.
17. The electrode structure of claim 16, wherein the lithium halide film is selected from lithium fluoride, lithium chloride, lithium bromide or lithium iodide.
18. The electrode structure of claim 16, wherein the lithium halide film is selected from lithium chloride and lithium bromide.
19. The electrode structure of claim 16, wherein the chalcogenide film is a bismuth chalcogenide film.
20. The electrode structure of claim 16, further comprising an anode film formed between the current collector and the lithium metal film.
Citation Information
Patent Citations
Lithium secondary battery
JP1992248276A
Negative electrode for lithium battery, its manufacturing method and lithium battery including the negative electrode
JP2004319489A
Lithium polymer secondary battery
JP2005129535A
Passivation film for solid electrolyte interface of three-dimensional copper-containing electrodes in energy storage devices
JP2012532419A
Electrophoretic deposition of thin-film batteries
JP2014500597A